The engineer’s Instruction to stake the connecting vertical plate of pre-engineering steel column - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the engineer’s Instruction to stake the connecting vertical plate of pre-engineering steel column of BRACU new campus project site.